Effect of different concentrations of nisin on starter culture of model Cheeses manufactured from ultrafiltrated milk - Kh Mohammadi (Bihdāsht-i Mavādd-i Ghaz̠āyī, 2013)
Nisin is a natural preservative produced by strains of Lactococcuslactis subsp. Lactis, has been approved for use in food by the Joint Food and Agricultural Organization/World Health Organization (FAO/WHO) Committee on Food Additives and has been awarded generally recognized as safe (GRAS). It remains the only bacteriocin allowed in food as an addedpreservative. Nisin has a broad spectrum of antimicrobial activity againstgram-positive bacteria, thus one of the problems associated with nisin application is inhibition of starter culture and prevention of ripening, which is required for development of cheese characteristics during ripening. In the current study, the effects of different concentrations of nisin and temperature on growth and activity of lactic acid bacteria in model cheeses manufactured from ultrafiltrated milk was evaluated. Cheese samples were supplemented with nisin at concentrations of 0, 2, 4 and 6 µg/g and stored at 8 and 25 °C up to 60 days. Microbiological and physico-chemical properties of the cheese samples were analyzedat 0, 1, 8, 15, 30, 45 and 60 days. Results showed that addition of nisin at concentrations of 4 and 6 µg/g affects (p